Military leadership and counterinsurgency the British Army and small war strategy since World War II - Nolan, Victoria (International library of security studies, 2012)
Between 1948 and 1960, the British army conducted three important counterinsurgency operations in Malaya, Kenya, and Cyprus. During that time, military leaders inspired the evolution of a distinct organizational culture, known as "small wars culture," which affected learning, discipline, and attitudes towards leadership and fellow soldiers. Using a synthesis of organizational theory and archival research, this book explores how military leaders embedded and transmitted this particular military organizational culture within the British army and provides an analysis of leaders' characteristics, their support networks and past experiences. This book will be of interest to counterinsurgency specialists, the British Army, and military historians and sociologists, as well as to serving military forces.